Prevalence of Darkling Beetles (Alphitobius diaperinus) and Bacterial Load in Broiler LittersPrevalence of Darkling Beetles (Alphitobius diaperinus) and Bacterial Load in Broiler Litters - Asaniyan, E.K.; Laseinde, E.A.O.; Agbede, J.O. (International Journal of Poultry Science, 2007)
The differently replaced litters (sand and wood shavings) on which broilers were raised for eight weeks were examined for bacterial loads and darkling beetle (Alphitobius diaperinus) population. The initial investigation into the litters revealed wood shavings to have higher bacterial load compared to sand. Litter replacement frequencies and litter type significantly affected (p